الثقافة التنظيمية وعلاقتها بسلوك المواطنة التنظيمية لدى العاملين بالمؤسسة الصناعية - بحري، صابر; خرموش، منى (جامعة عنابة, 2020)
هدفت هذه الدراسة إلى معرفة العلاقة بين الثقافة التنظيمية وسلوك المواطنة التنظيمية لدى العاملين بالمؤسسة الصناعية، ولتحقيق هدف الدراسة استخدمنا مقياسين الأول خاص بالثقافة التنظيمية والثاني خاص بسلوك المواطنة التنظيمية على عينة مكونة من 171 عامل من مؤسسة عين كبيرة للإسمنت بولاية سطيف، اعتمدنا على المنهج الوصفي، وقد أسفرت الدراسة إلى أن هناك علاقة ارتباطية قوية جدا وموجبة بين الثقافة التنظيمية وسلوك المواطنة التنظيمية لدى عينة الدراسة. This study aimed to know the nature of the relationship between the organizational culture and the behavior of organizational citizenship among workers in an industrial institution. For that reason, we chose the descriptive method and used two measures, the first one for organizational culture and the second one for organizational citizenship behavior. These two research tools were distributed to 171 workers working in the cement factory in Ain al-Kabira Setif Department. This study was able to obtain the most important results: a very strong positive relationship between the organizational culture and the behavior of organizational citizenship.
Keywords: المواطنة التنظيمية -- المؤسسات الصناعية -- الهوية الوطنية -- الثقافة التنظيمية